Environmental and socioeconomic evaluation of lithium mining: Proposed methodology and its application to Chilean projects - Guerrero, Valentina Canales; Alvarado, Felipe Díaz; Yamaguchi, Rintaro (European Journal of Sustainable Development, 2025)
Lithium is critical for a sustainable energy transition, particularly regarding the battery market. For decades, traditional extraction methods from brine have adversely affected inland wetlands, which are considered fragile ecosystems. For instance, brine extraction in Chile has severely decreased the populations of three flamingo species and obstructed the livelihoods of indigenous communities. However, these negative externalities have not been included in the evaluation of lithium brine mining projects. The novelty of this study lies in developing a methodology to consistently quantify environmental and social impacts in monetary values. Moreover, the study will compare three metallic lithium production processes, including direct lithium extraction (DLE) technologies. The methodology determines how these processes disrupt ecosystem services and affect the environmental, economic, social, and process efficiency dimensions. Some impacts are measured using market and non-market valuations. Our results directly provide valuable insights to the recently developed Chilean National Lithium Strategy, which seeks to establish a sustainable, technological, and socio-economic framework for lithium production. Key Words: Energy transition, Valuation, Wetlands, Ecosystem services, Lithium mining, Direct lithium extraction.